Catalyst component for olefin polymerization, catalyst and application thereof

By using chloromycin compounds combined with magnesium and titanium compounds to form a catalyst component with high activity and good stereospecificity, the problems of insufficient internal electron donor activity and insufficient environmental friendliness in the existing technology are solved, and the problem is achieved Efficient olefin polymerization and broader polypropylene molecular weight distribution.

CN119331140AActive Publication Date: 2025-01-21PETROCHINA CO LTD
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
CN202310897635.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-21
Publication Date
2025-01-21
Estimated Expiration
2043-07-21

AI Technical Summary

Technical Problem

In the prior art, the internal electron donor compound as an olefin polymerization catalyst has problems such as insufficient activity, poor stereo orientation and insufficient environmental friendliness, especially phthalate compounds are harmful to the environment and human health.

Method used

Chlorostrobin compounds are used as internal electron donors and combined with magnesium and titanium compounds to form a catalyst component for olefin polymerization. The catalyst component reacts at high temperatures to form a catalyst with high activity and good stereospecificity.

Benefits of technology

The catalyst achieves high activity and good stereospecificity, and the resulting polypropylene has regular particle size, high packing density, high isotacticity, wider molecular weight distribution, and avoids the use of harmful phthalate compounds.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331140A_ABST
    Figure CN119331140A_ABST
Patent Text Reader

Abstract

The invention provides a catalyst component for olefin polymerization, a catalyst and application thereof. The catalyst component is prepared from the following components: Mg, Ti, halogen and chlorendic acid ester internal electron donors, wherein the chlorendic acid ester internal electron donor has a structure as shown in a formula I: # imgabs0 #, the catalyst component and the catalyst have high catalytic activity, polypropylene obtained by catalytic polymerization has regular particle size, high bulk density and high isotacticity, the molecular weight distribution of polypropylene obtained by catalytic polymerization is wider than that of polypropylene obtained by phthalate and diether catalysts, and the molecular weight distribution of polypropylene obtained by the catalyst component and the catalyst is larger than that of polypropylene obtained by the phthalate and diether catalysts. Better comprehensive performance is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a solid catalyst component and a catalyst for olefin polymerization, and a preparation method and application thereof, belonging to the field of polyolefin catalysts. Background Art

[0002] At present, Ziegler-Natta catalysts (ZN catalysts) still occupy a dominant position in polyolefin production. The development focus of most ZN catalysts is on the development of highly active and highly stereospecific catalysts and improving the copolymerization ability of catalysts. In addition, due to the high catalytic efficiency of traditional ZN catalysts (transition metal compounds such as titanium chemically bonded to a magnesium-containing carrier), the polymer produced has good comprehensive performance and low cost. At present, most catalysts for producing polypropylene in the world are still based on ZN catalytic systems, which are characterized by high activity, high stereoregularity, long life and customized product structure. From the development process of ZN catalysts, it can be seen that as early as the emergence of the first generation of catalysts, it was found that adding a third component (mostly electron donors, also known as Lewis bases, among which those added during the catalyst preparation process are called internal electron donors, and those added during the polymerization process are called external electron donors) will have a great influence on the polymerization behavior of olefins and the properties of polymers; changing the internal electron donor in the catalyst can change the properties of the catalyst active center to the greatest extent possible, thereby changing the performance of the catalyst to the greatest extent. Therefore, the development of new electron donors has always been a hot spot in the research and development of ZN polypropylene catalysts.

[0003] The relatively distinctive high-performance internal electron donor compounds in the prior art mainly include: (1) fatty acid esters and aromatic acid ester compounds, mainly represented by phthalate compounds; (2) diether compounds (for example, compounds disclosed in EP0361493 and EP0728724); (3) succinate compounds (for example, compounds disclosed in WO9856834, WO0063261, and WO03022894); (4) glycol ester compounds (for example, compounds disclosed in WO9856834, WO0063261, and WO03022894); (5) compounds with other functional groups (for example, compounds disclosed in CN1105671, CN1242780, and US20060128558), etc. However, in practical applications, the above compounds have certain problems as internal electron donors for olefin polymerization catalysts. Although the catalysts using 1,3-diether compounds as internal electron donors have higher activity and good hydrogen tuning sensitivity, the relative molecular mass distribution of the produced PP is narrow, which is not conducive to the development of different grades of PP; the advantage of using succinate compounds as internal electron donors is that the relative molecular mass distribution of the synthesized PP is relatively wide, but the disadvantage is that the stereoregularity of PP and the hydrogen tuning sensitivity of the catalyst need to be improved; and the overall activity of the diol ester catalytic system is not as ideal as the diether system.

[0004] At present, the most widely used polyolefin internal electron donor in industry is phthalate compounds, which have medium catalyst activity, good stereoselectivity and low price. However, phthalate compounds, as commonly used plasticizers, have great harm to human reproductive health and the environment, and there is a great demand for replacement. At present, the use of most phthalate substances has been restricted. Therefore, it is one of the common research and development goals in the field of polyolefin catalysts in recent years to develop a new electron donor with excellent activity, good stereospecificity, good comprehensive performance and low cost to replace the phthalate electron donor compounds widely used in the prior art and apply them to the preparation of efficient Ziegler-Natta catalysts. Summary of the invention

[0005] In order to solve the above problems, the purpose of the present invention is to provide a catalyst component, a catalyst and its application for olefin polymerization. The catalyst component and the catalyst have high catalytic activity, and the polypropylene obtained by catalytic polymerization has regular particle size, high bulk density, high isotacticity, wider molecular weight distribution than that of polypropylene obtained by phthalate and diether catalysts, and has better comprehensive performance.

[0006] In order to achieve the above object, the present invention provides a catalyst component for olefin polymerization, which comprises: Mg, Ti, halogen, and a chloranilate internal electron donor; wherein the chloranilate internal electron donor has a structure shown in Formula I:

[0007]

[0008] In Formula I, R 1 and R 2 are the same or different, each independently selected from hydrogen, halogen, C 1 -C 20 Preferably, R 1 and R 2 Each of the above mentioned heteroatoms contains one or more heteroatoms selected from halogen, N, O, S, P and Si; more preferably, R 1 and R 2 Bonded to each other to form a ring.

[0009] According to a specific embodiment of the present invention, preferably, in Formula I, R 1 and R 2the same or different, each independently selected from H, halogen, the following substituents with less than 20 carbon atoms: straight-chain or branched alkyl, cycloalkyl, alkenyl, ester, phenyl, alkylphenyl, phenylalkyl, indenyl, benzyl, halogenated alkyl, alkyl containing heteroatoms, halogenated cycloalkyl, cycloalkyl containing heteroatoms, halogenated phenyl, phenyl containing heteroatoms, halogenated alkylphenyl, alkylphenyl containing heteroatoms, halogenated phenylalkyl, phenylalkyl containing heteroatoms, halogenated indenyl, indenyl containing heteroatoms, halogenated benzyl, benzyl containing heteroatoms, heterocyclic aromatic substituents; the heteroatoms include one or a combination of two or more of N, O, S, P, and Si.

[0010] According to a specific embodiment of the present invention, preferably, in Formula I, R 1 and R 2 are each independently selected from H, halogen, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, cyclopentyl, n-hexyl, cyclohexyl, heptyl, octyl, nonyl, decyl, C 11 -C 20 The straight chain or branched alkyl group of 20 carbon atoms or the following substituents within 20 carbon atoms: alkenyl, phenyl, m-chlorophenyl, p-chlorophenyl, o-chlorophenyl, m-methoxyphenyl, p-methoxyphenyl, o-methoxyphenyl, p-methylphenyl, p-nitrophenyl, m-nitrophenyl, benzyl and its derivatives, phenethyl and its derivatives, furyl, pyrrolyl, thienyl and indenyl; more preferably, the alkenyl group includes propenyl, butenyl, pentenyl and hexenyl.

[0011] According to a specific embodiment of the present invention, preferably, the chlorendic acid ester internal electron donor includes dimethyl chlorendic acid, diethyl chlorendic acid, di-n-propyl chlorendic acid, diisopropyl chlorendic acid, di-n-butyl chlorendic acid, diisobutyl chlorendic acid, di-tert-butyl chlorendic acid, di-n-pentyl chlorendic acid, diisopentyl chlorendic acid, dicyclopentyl chlorendic acid, di-n-hexyl chlorendic acid, dicyclohexyl chlorendic acid, diheptyl chlorendic acid, dioctyl chlorendic acid, dinonyl chlorendic acid, didecyl chlorendic acid, diundecyl chlorendic acid, didodecyl chlorendic acid, ditridecyl chlorendic acid, ditetradecyl chlorendic acid, dipentadecyl chlorendic acid, dihexadecyl chlorendic acid, diheptadecyl chlorendic acid, di- The invention can be selected from the group consisting of chlorendic acid (octadecyl) ester, chlorendic acid di(nonadecyl) ester, chlorendic acid di(eicosyl) ester, chlorendic acid diphenyl ester, chlorendic acid di-m-chlorophenyl ester, chlorendic acid di-p-chlorophenyl ester, chlorendic acid di-o-chlorophenyl ester, chlorendic acid di-p-tolyl ester, chlorendic acid di-m-tolyl ester, chlorendic acid di-o-tolyl ester, chlorendic acid di(mesitylene) ester, chlorendic acid di-p-methoxyphenyl ester, chlorendic acid di-m-methoxyphenyl ester, chlorendic acid di-o-methoxyphenyl ester, chlorendic acid di-p-nitrophenyl ester, chlorendic acid di(α-furan)methyl ester, chlorendic acid di(5-pentene) ester, chlorendic acid di(α-thiophene) ester, chlorendic acid dibenzyl ester, chlorendic acid diphenylethyl ester, chlorendic acid dicinnamyl ester, chlorendic acid ditetrahydrofurfuryl ester, and chlorendic acid di(1-indenyl) alcohol ester, or a combination of two or more thereof.

[0012] The chlorendic acid ester compound shown in formula I can be obtained by esterification reaction using chlorendic acid as a raw material, as shown in the following reaction formula I, which only requires one step of reaction, is simple to synthesize, and has a high yield; when performing the esterification reaction, the raw material alcohol can be an alcohol (R 1 and R 2 Same situation) or two alcohols (R 1 and R 2 Different situations), when two alcohols are used, a mixture of three chlorendonates can be obtained, which can be directly used as an internal electron donor without separation. The ratio of each component in the mixture can be adjusted by the addition ratio of the two alcohols in the reaction raw materials, and the ratio of each component can be characterized and determined by analytical methods such as chromatography-mass spectrometry and nuclear magnetic resonance;

[0013]

[0014] According to a specific embodiment of the present invention, preferably, the catalyst component comprises a titanium compound, a magnesium compound, and an internal electron donor as shown in formula I; the precursor of the magnesium compound is selected from X n Mg(OR a ) 2-n MgCl 2 ·mR a OH, R a 2-n MgX n MgCl 2 / SiO 2 MgCl 2 / Al 2 O 3 , a mixture of magnesium halide and titanium alkoxide, or a combination of two or more thereof, wherein m is 0.1-6, 0≤n≤2, X is a halogen, R a C 1 -C 20 The general formula of the titanium compound is TiX N (OR b ) 4-N , where R b C 1 -C 20 The hydrocarbon group is: X is halogen, and N is 1-4.

[0015] According to a specific embodiment of the present invention, preferably, the magnesium compound is an alcoholate of magnesium dihalide; or, the magnesium compound is a liquid magnesium compound (a magnesium compound dissolved in a liquid); or, the magnesium compound is a derivative of a magnesium dihalide molecule in which at least one halogen atom is replaced by a hydrocarbonoxy group or a halogenated hydrocarbonoxy group; more preferably, it is a hydrocarbonoxy magnesium compound, and further preferably, an alkoxy magnesium and / or an aryloxy magnesium.

[0016] According to a specific embodiment of the present invention, preferably, the titanium compound includes one or a combination of two or more of titanium tetrachloride, titanium tetrabromide, titanium tetraiodide, and alkoxy titanium halide.

[0017] According to a specific embodiment of the present invention, preferably, the alkyl titanium halide includes one or a combination of two or more of methoxytitanium trichloride, ethoxytitanium trichloride, propoxytitanium trichloride, n-butoxytitanium trichloride, dimethoxytitanium dichloride, diethoxytitanium dichloride, dipropoxytitanium dichloride, di-n-butoxytitanium dichloride, trimethoxytitanium chloride, triethoxytitanium chloride, tripropoxytitanium chloride, and tri-n-butoxytitanium chloride.

[0018] According to a specific embodiment of the present invention, preferably, the titanium compound is titanium tetrachloride.

[0019] According to a specific embodiment of the present invention, preferably, the molar ratio of the internal electron donor represented by formula I to the magnesium compound calculated as magnesium element is 0.01-5.0:1, preferably 0.05-3.0:1.

[0020] The present invention does not particularly limit the preparation method of the above-mentioned solid catalyst component, which can be carried out according to the following methods:

[0021] Method 1: Magnesium alcoholate or magnesium chloroalcoholate and excess TiCl 4 and an internal electron donor compound, reacting at a temperature of 80°C to 135°C; preferably, the general formula TiX N (OR b ) 4-N Titanium compounds (where R b C 1 -C 20 A hydrocarbon group, X is a halogen, N = 1-4; preferably TiCl 4 ) and the general formula is MgCl 2 ·mR a OH adduct (wherein m is a number of 0.1-6, preferably 2-4, and R a C 1 -C 20 The solid catalyst component is prepared by reacting an internal electron donor with a hydrocarbon group; wherein the general formula is MgCl 2 ·mR a The adduct of OH can be suitably made into spherical shape by the following method: in the presence of an inert hydrocarbon immiscible with the adduct, alcohol and magnesium chloride are mixed, and the emulsion is rapidly quenched, thereby solidifying the adduct in the form of spherical particles (refer to the disclosures of US4399054 and US4469648). The spherical adduct obtained in this way can be directly reacted with the titanium compound, or it can be previously subjected to heat-controlled dealcoholation (80°C-130°C) to obtain a dealcoholated adduct (wherein the molar number of alcohol is generally less than 3, preferably between 0.1-2.5), and then subjected to the subsequent reaction;

[0022] For example, the adduct or dealcoholate adduct is suspended in cold TiCl 4 (generally -25°C-0°C) to react with the titanium compound, heating the mixture to 80°C-130°C and maintaining it at this temperature for 0.5-2 hours, wherein the TiCl 4 The treatment can be performed once or multiple times, and the TiCl 4 An internal electron donor compound may be added during the treatment, and the treatment may be repeated one or more times;

[0023] Method 2: Dissolve the magnesium compound in a solvent system consisting of an organic epoxy compound, an organic phosphine compound and an inert diluent to form a uniform solution, and then mix it with a titanium compound, and precipitate a solid in the presence of a precipitation aid; the solid is treated with an internal electron donor compound to load the internal electron donor compound on the solid, and if necessary, further treated with titanium tetrahalide and an inert diluent; the precipitation aid is one of an organic anhydride, an organic acid, an ether, and a ketone. The components are calculated per mole of magnesium halide, and the organic epoxy compound is 0.2-10 mol, the organic phosphine compound is 0.1-3 mol, the precipitation aid is 0-1.0 mol, and the Ti compound is 0.5-150 mol (calculated as mole of titanium element);

[0024] Method 3: Using TiCl 4 or an aromatic hydrocarbon solution of titanium alkoxide (e.g. toluene, xylene, etc.) is reacted with a dihydrocarbyl magnesium compound such as dialkoxy magnesium (preferably diethoxy magnesium) or diaryloxy magnesium at -25-0°C and halogenated at 80-130°C. The TiCl 4 The treatment with the aromatic hydrocarbon solution can be repeated once or multiple times, and the internal electron donor compound can be added once or in batches during multiple such treatments. For example, the preparation method of the titanium-containing solid catalyst component disclosed in US5077357 can be referred to: ethoxymagnesium, tetraethoxytitanium, o-cresol, ethanol and chlorobenzene are added in sequence and stirred; TiCl 4 / chlorobenzene solution is quickly added to the above liquid, and the temperature is raised until it is completely dissolved, and then the temperature is continued to be raised to a specific temperature; using N 2 After bubbling away the ethanol reactant, continue stirring for a certain period of time, then wash once with hot chlorobenzene, wash twice with isooctane, and then N 2 The carrier can be obtained by drying. Or according to another example: TiCl 4 , tetraethoxytitanium, ethoxymagnesium and o-cresol are added to chlorobenzene and stirred; ethanol is added and stirred for 3 hours at high temperature after the ethoxymagnesium is dissolved; hot filtering is then washed once with warm chlorobenzene, once with isooctane, and finally N 2 dry;

[0025] Method 4: Pre-activate magnesium dichloride according to the existing method, and then use excess TiCl 4 treatment, wherein an internal electron donor compound is contained in the solution. 4 The solid was treated several times and washed with hexane to remove any unreacted TiCl 4 ;

[0026] Method 5: Prepare with reference to the preparation method of titanium-containing solid catalyst component disclosed in CN1208045: first, a liquid magnesium compound and a liquid titanium compound are contacted at low temperature in the presence of a compound selected from alcohols, phenols, ketones, aldehydes, ethers, amines, pyridines and esters to precipitate a solid, the contact temperature is generally -70°C to 200°C, preferably -30°C to 130°C, and an internal electron donor compound is used during the contact process;

[0027] Method 6: Grind anhydrous magnesium chloride and an internal electron donor compound together under conditions where magnesium dichloride is activated. The product obtained can be treated with excess TiCl 4 The method is further described as follows: the product obtained by co-grinding magnesium dichloride, a titanium compound and an internal electron donor compound in an anhydrous state is treated with a halogenated hydrocarbon such as 1,2-dichloroethane, chlorobenzene, dichloromethane, etc., the treatment being carried out at a temperature between 40°C and the boiling point of the halogenated hydrocarbon for 1-4 hours, and then the product is usually washed with an inert hydrocarbon solvent such as hexane;

[0028] Method 7: Using SiO 2 The magnesium compound supported on inorganic oxides such as MgO, alumina or porous silica gel is used as a carrier, and then activated by a well-known method, and then an excess of TiCl 4 treatment, during which an internal electron donor compound is added.

[0029] The reaction of the above catalyst components leads to the formation of magnesium halide in an active form; general crystalline magnesium halide has a regular structure and can carry very little Ti, so the catalytic activity is low. To prepare a highly active supported catalyst, the magnesium halide must be activated; the activation treatment method includes using physical and / or chemical methods to make it into microcrystals so that the active center is loaded on the surface, edge and defect of the magnesium halide. The treated magnesium halide microcrystal suitable for loading Ti is "active magnesium halide". In addition to these reactions, other methods are also known in the literature to make compound starting materials other than magnesium halide form magnesium halide in an active form.

[0030] In any of the methods for preparing the catalyst components, the internal electron donor compound can be added directly as such or prepared in an alternative manner, such as by using a suitable precursor in situ, which can be converted into the desired internal electron donor compound, for example, by known chemical reactions such as esterification, transesterification, etc. 2In terms of molar number, the internal electron donor compound is used in a molar ratio of 0.01-5:1, preferably 0.05-3.0:1; in addition, the internal electron donor compound can be added simultaneously or separately in the preparation process in one batch or in batches, in any order and in any combination.

[0031] The present invention also provides a catalyst for olefin polymerization, which comprises the above catalyst component and an organic aluminum compound.

[0032] According to a specific embodiment of the present invention, preferably, the general formula of the organoaluminum compound is AlR c p X (3-p) , where R c is hydrogen or C 1 -C 20 wherein X is a halogen and p is an integer of 0≤p≤3.

[0033] According to a specific embodiment of the present invention, preferably, the organoaluminum compound includes one or a combination of two or more of trialkylaluminum compounds, alkylaluminum halides, alkylaluminum hydrides, alkylaluminum sesquichlorides, and alkylaluminoxanes.

[0034] According to a specific embodiment of the present invention, preferably, the trialkylaluminum compound includes one or a combination of two or more of trimethylaluminum, triethylaluminum, triisobutylaluminum, tri-n-butylaluminum, tri-n-hexylaluminum, and trioctylaluminum; the alkylaluminum halide includes AlEt 2 Cl; the alkylaluminum sesquichloride comprises Al 2 Et 3 Cl 3 More preferably, the organoaluminum compound is AlEt 2 Cl and Al 2 Et 3 Cl 3 mixture.

[0035] According to a specific embodiment of the present invention, preferably, the molar ratio of the organic aluminum compound to the titanium atom in the catalyst component is 1-1000:1, more preferably 50-800:1.

[0036] According to a specific embodiment of the present invention, preferably, the raw material composition of the catalyst also includes an external electron donor.

[0037] According to a specific embodiment of the present invention, preferably, the external electron donor is a siloxane compound.

[0038] According to a specific embodiment of the present invention, preferably, the general formula of the siloxane compound is R' t Si(OR”) 4-t, wherein R' and R" are each independently selected from C 1 -C 18 A hydrocarbon group, t is an integer of 0≤t≤3.

[0039] According to a specific embodiment of the present invention, preferably, R' and R" each contain a heteroatom; more preferably, the heteroatom includes one or a combination of two or more of N, O, S, P, and Si.

[0040] According to a specific embodiment of the present invention, preferably, the siloxane compound includes trimethylmethoxysilane, trimethylethoxysilane, tri-n-propylmethoxysilane, tri-n-propylethoxysilane, tri-n-butylmethoxysilane, triisobutylethoxysilane, tricyclohexylmethoxysilane, tricyclohexylethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, di-n-propyldimethoxysilane, diisopropyldimethoxysilane, di-n-propyldiethoxysilane, diisopropyldiethoxysilane, di-n-butyldiethoxysilane, diisobutyldiethoxysilane, di-tert-butyldimethoxysilane, di-tert-butyldimethoxysilane, di-n-butyldimethoxysilane, diisobutyldimethoxysilane silane, di-tert-butyldiethoxysilane, di-n-butyldiethoxysilane, n-butylmethyldimethoxysilane, di(2-ethylhexyl)dimethoxysilane, di(2-ethylhexyl)diethoxysilane, dicyclohexyldimethoxysilane, dicyclohexyldiethoxysilane, dicyclopentyldimethoxysilane, dicyclopentyldiethoxysilane, cyclohexylmethyldimethoxysilane, cyclohexylmethyldiethoxysilane, cyclohexylethyldimethoxysilane, cyclohexylisopropyldimethoxysilane, cyclohexylethyldiethoxysilane, cyclopentylmethyldimethoxysilane, cyclopentylethyldiethoxysilane, cyclopentylisopropyldiethoxysilane, cyclopentylisobutyldimethoxysilane, cyclohexyl-n-propyl Dimethoxysilane, cyclohexyl-n-propyldiethoxysilane, cyclohexyl-n-butyldiethoxysilane, amylmethyldimethoxysilane, amylmethyldiethoxysilane, amylethyldimethoxysilane, amylethyldiethoxysilane, cyclohexyldimethylmethoxysilane, cyclohexyldiethylmethoxysilane, cyclohexyldiethylmethoxysilane, cyclohexyldiethylethoxysilane, 2-ethylhexyltrimethoxysilane, cyclohexyldimethoxysilane, cyclohexyldiethoxysilane, 2-ethylhexyltriethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, isopropyltrimethoxysilane, isopropyltriethoxysilane, n-butyl trimethoxysilane, isobutyltrimethoxysilane, tert-butyltrimethoxysilane, n-butyltriethoxysilane, cyclohexyltrimethoxysilane, cyclohexyltriethoxysilane, cyclopentyltrimethoxysilane, cyclopentyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, 2-ethylhexyltrimethoxysilane, 2-ethylhexyltriethoxysilane, pentyltrimethoxysilane, pentyltriethoxysilane, tetramethoxysilane, tetraethoxysilane, cyclohexylcyclopentyldimethoxysilane, cyclohexylcyclopentyldiethoxysilane, cyclohexylcyclopentyldipropoxysilane, 3-methylcyclohexylcyclopentyldimethoxysilane, 4-methylcyclohexylcyclopentyldimethoxysilane, 3,5-dimethylcyclohexylcyclopentyldimethoxysilane, 3-methylcyclohexylcyclohexyldimethoxysilane, bis(3-methylcyclohexyl)dimethoxysilane, 4-methylcyclohexylcyclohexyldimethoxysilane, bis(4-methylcyclohexyl)dimethoxysilane, 3,5-dimethylcyclohexylcyclohexyldimethoxysilane, bis(3,5-dimethylcyclohexyl)dimethoxysilane, tetrapropoxysilane, tetrabutoxysilane, or a combination of two or more thereof.

[0041] According to a specific embodiment of the present invention, preferably, the siloxane compound includes di-n-propyl dimethoxysilane, diisopropyl dimethoxysilane, di-n-butyl dimethoxysilane, diisobutyl dimethoxysilane, di-tert-butyl dimethoxysilane, di-n-butyl diethoxysilane, tert-butyl trimethoxysilane, dicyclohexyl dimethoxysilane, dicyclohexyl diethoxysilane, cyclohexyl methyl dimethoxysilane, cyclohexyl ethyl diethoxysilane, One or a combination of two or more of cyclohexylethyldimethoxysilane, cyclohexylethyldiethoxysilane, cyclopentylmethyldimethoxysilane, cyclopentylmethyldiethoxysilane, cyclopentylethyldimethoxysilane, cyclohexylcyclopentyldimethoxysilane, cyclohexylcyclopentyldiethoxysilane, 3-methylcyclohexylcyclopentyldimethoxysilane, 4-methylcyclohexylcyclopentyldimethoxysilane and 3,5-dimethylcyclopentyldimethoxysilane.

[0042] According to a specific embodiment of the present invention, preferably, the siloxane compound includes cyclohexylmethyldimethoxysilane, diisopropyldimethoxysilane, di-n-butyldimethoxysilane, diisobutyldimethoxysilane, diphenyldimethoxysilane, phenyltriethoxysilane, methyl-tert-butyldimethoxysilane, dicyclopentyldimethoxysilane, 2-ethylpiperidinyl-2-tert-butyldimethoxysilane, (1,1,1-trifluoro-2-propyl)-2-ethylpiperidinyldimethoxysilane, (1,1,1-trifluoro-2-propyl)-methyl-methoxysilane, cyclohexyltrimethoxysilane, tert-butyltrimethoxysilane, tert-hexyltrimethoxysilane, or a combination of two or more thereof.

[0043] According to a specific embodiment of the present invention, preferably, the molar ratio of silicon in the external electron donor to titanium in the catalyst component is 0.002-100:1, more preferably 0.01-20:1, and further preferably 0.01-5:1.

[0044] The invention also provides application of the catalyst in olefin polymerization.

[0045] According to a specific embodiment of the present invention, preferably, the olefin includes a linear or branched olefin, such as ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 3-methyl-1-butene, 4-methyl-1-pentene, butadiene, vinylcyclopentene, vinylcyclohexene, one or a combination of two or more thereof.

[0046] According to a specific embodiment of the present invention, preferably, the polymerization comprises ethylene and / or propylene polymerization.

[0047] According to a specific embodiment of the present invention, preferably, the polymerization includes homopolymerization or copolymerization.

[0048] According to a specific embodiment of the present invention, preferably, during the catalytic process, the order of adding the components in the catalyst is arbitrary, preferably the organoaluminum compound is first added to the polymerization system, then the external electron donor is added, and finally the catalyst component is added.

[0049] According to a specific embodiment of the present invention, preferably, in the above application, the polymerization process can be carried out with or without a solvent; the olefin monomer can be in gas phase or liquid phase; more preferably, hydrogen can be further added as a molecular weight regulator (polymerization can also be carried out without a molecular weight regulator); continuous polymerization or batch polymerization process can be applied, and the polymerization reaction can be carried out in one step, two steps or multiple steps.

[0050] According to a specific embodiment of the present invention, preferably, the polymerization temperature is ≤200°C, more preferably 20-100°C, and further preferably 40-80°C; the polymerization pressure is ≤10MPa, more preferably 0.3-5MPa.

[0051] The present invention has the following beneficial effects:

[0052] The invention provides a catalyst component with chloranil ester as an internal electron donor. Chloranil ester uses chloranil acid as a raw material, and undergoes an esterification reaction with alcohol under acidic conditions to obtain chloranil ester. The final product can be obtained by only one-step reaction. The synthesis is simple, the yield is high, and the cost is low, which is conducive to industrial production and application. The ester substituents of chloranil ester compounds are diverse, and the activity of the prepared catalyst is generally higher than that of the phthalate catalyst commonly used in industry today, and higher than that of the diether catalyst. The polypropylene obtained by catalytic polymerization using the catalyst of the invention has high isotacticity and a wider molecular weight distribution than that of the polypropylene obtained by the phthalate and diether catalysts. The polyolefin catalyst prepared by using the chloranil ester internal electron donor can avoid the use of the phthalate internal electron donor with reproductive and environmental toxicity, and has better comprehensive performance, and has broader industrial application prospects in countries and regions where the use of phthalate plasticizers is restricted. DETAILED DESCRIPTION

[0053] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.

[0054] The operations for preparing the catalysts in the following examples were all carried out under the protection of high-purity nitrogen.

[0055] The isotacticity of a polymer is determined by the heptane extraction method (extraction with boiling heptane for 6 hours): two grams of a dry polymer sample is placed in an extractor and extracted with boiling heptane for 6 hours. The residue is then dried to a constant weight, and the ratio of the obtained polymer weight (g) to 2 is the isotacticity.

[0056] The bulk density of the polymer was determined using the JB / T 2412-2008 method.

[0057] The molecular weight distribution of the polymer was determined by a PL-220 gel permeation chromatograph using trichlorobenzene as solvent at 150°C (standard sample: polystyrene, flow rate 1.0 mL / min, column: 3×Plgel 10um M1Xed-B 300×7.5 nm).

[0058] Preparation Example Synthesis of Chlorendamide Compounds Shown in Formula I

[0059] 1. The synthesis of dimethyl chlorendic acid is as follows:

[0060] In a 500L three-necked flask, chlorendic acid (3.9 g), methanol (100 mL), and concentrated sulfuric acid (0.6 mL) were added; heated to reflux for 2 hours; cooled to room temperature; the reaction solution was poured into a saturated sodium bicarbonate solution, extracted twice with ethyl acetate (100 mL × 2), the organic phases were combined, washed with saturated brine (100 mL × 2), concentrated and recrystallized to obtain the product chlorendic acid dimethyl ester (a1), the structure and H NMR spectrum results are shown in Table 1.

[0061] 2. Other chlorendic acid ester compounds (a2-a22) were prepared by the same synthesis method, using chlorendic acid as a raw material, and esterifying with the corresponding alcohol under acidic conditions to obtain the corresponding chlorendic acid ester. The structures and H NMR spectra of compounds a2-a22 are shown in Table 1.

[0062]

[0063] Table 1

[0064]

[0065]

[0066]

[0067] Example 1

[0068] This embodiment provides a catalyst component, and the preparation method thereof is as follows:

[0069] In a 500 ml 5-necked flask with stirring and fully replaced with nitrogen, add 10 g MgCl 2 2.5C 2 H 5 OH microspheres and 150mL titanium tetrachloride were used to prepare a suspension, then maintained at -15°C for 1 hour, slowly heated to 80°C, 4.2g (10mmol) of dimethyl chlorendonate was added, and then the temperature was continued to rise to 110°C and kept constant for 1 hour, and then the liquid was filtered clean, and the obtained solid was washed 3 times with 120mL titanium tetrachloride at 110°C, and then washed 4 times with 150mL hexane at 60°C, and finally the liquid was filtered off and dried to obtain a solid catalyst component E1. The titanium content, internal electron donor content and polymerization data of the solid catalyst component are shown in Table 2.

[0070] Example 2-22

[0071] Examples 2-22 each provide a catalyst component E2-E22, the preparation process of which is as shown in Example 1, except that dimethyl chlorendic acid is replaced with 10 mmol of compounds a2-a22 in Table 1 in sequence.

[0072] Embodiment 23

[0073] This embodiment provides a catalyst component, and the preparation method thereof is as follows:

[0074] In a 500 ml 5-necked flask fully replaced with nitrogen and with stirring, 10 g of anhydrous magnesium chloride, 150 mL of toluene, 17 mL of epichlorohydrin and 16 mL of tributyl phosphate were added at room temperature, and the temperature was raised to 50° C. with stirring and maintained for 2 hours. The solid was completely dissolved, and then 2.40 g of phthalic anhydride was added and maintained for another hour; the solution was cooled to -25° C., 110 mL of titanium tetrachloride was added dropwise within 1 hour, and the temperature was slowly raised to 80° C. During the heating process, the solid was gradually washed out, 4.4 g of diethyl chlorendonate was added, and the temperature was maintained at 80° C. for 1 hour; after filtering, it was washed twice with 200 mL of toluene, and then 120 mL of toluene and 80 mL of titanium tetrachloride were added, and the temperature was continued to rise to 110° C. and kept constant for 2 hours, and then the liquid was filtered clean, and the treatment was repeated once, and the liquid was filtered off. The obtained solid was washed once with 100 mL of dichloroethane and 4 times with hexane, and the solid catalyst component E23 was obtained after drying. The titanium content, internal electron donor content and polymerization data of the solid catalyst component are shown in Table 2.

[0075] Embodiment 24

[0076] This embodiment provides a catalyst component, and the preparation method thereof is as follows:

[0077] In a 500ml 5-necked flask with nitrogen fully replaced and stirred, 8g of diethoxymagnesium and 100mL of toluene were added to prepare a suspension, 25mL of titanium tetrachloride was added dropwise at -15°C, the temperature was slowly raised to 0°C after the addition was completed, and 50mL of titanium tetrachloride was added dropwise, and then the temperature was slowly raised to 80°C, 4.4g of diethyl chlorendic acid was added, and the temperature was continued to rise to 110°C and kept constant for 2 hours, and then the liquid was filtered clean, the liquid was filtered off, and the obtained solid was washed 3 times with 100mL of titanium tetrachloride at 125°C, and then washed 4 times with 120mL of hexane at 60°C, the liquid was filtered off and dried to obtain a solid catalyst component E24. The titanium content, internal electron donor content and polymerization data of the solid catalyst component are shown in Table 2.

[0078] Comparative Example 1

[0079] This comparative example provides a catalyst component D1, and its preparation process is the same as that of Example 1, except that dimethyl chlorendic acid is replaced by 10 mmol of di-n-butyl phthalate (DN).

[0080] Comparative Example 2

[0081] This comparative example provides a catalyst component D2, and its preparation process is the same as that of Example 1, except that dimethyl chlorendic acid is replaced by 10 mmol of 9,9-dimethoxyfluorene (FLU).

[0082] polymerization

[0083] The above-obtained catalyst component was used as a component of an olefin polymerization catalyst to carry out polymerization evaluation:

[0084] After nitrogen is fully replaced in a 5L stainless steel reactor, 5mL of 0.5mol / L triethylaluminum hexane solution and 1mL of 0.1mol / L methylcyclohexyldimethoxysilane hexane solution and 10mg of the prepared catalyst component are added, and then 10mL of hexane is added to flush the feed line, and then 2L (under standard conditions) of hydrogen and 2.5L of refined propylene are added, and the reaction is controlled to prepolymerize at 25°C for 5 minutes, and the temperature is raised to 70°C, and the polymerization reaction is carried out at this temperature for 1 hour. After the reaction is completed, the reactor is cooled and stirring is stopped, the reaction product is discharged, and the polymer is obtained by drying. The polymerization data is shown in Table 2.

[0085] Table 2

[0086]

[0087]

[0088] The catalyst components of the chlorendonate compounds containing different substituents as internal electron donors in Examples 1-22 are all higher in activity than the most commonly used internal electron donor catalyst in industry (the catalyst component of the phthalate internal electron donor in Comparative Example 1) under the same preparation conditions, and higher than the diether catalyst in Comparative Example 2, and have good stereoselectivity, high isotacticity of the obtained polymer, wider molecular weight distribution of polypropylene than that of polypropylene using phthalate and diether catalysts, and regular polymer particle size and high bulk density. Examples 23 and 24 are catalyst components prepared by using chlorendonate compounds using different preparation methods, and also show excellent performance of high activity and high stereoselectivity.

Claims

1. A catalyst component for olefin polymerization, comprising: Mg, Ti, halogens, chloranilates as internal electron donors; in, The chlorendic acid ester internal electron donor has a structure shown in Formula I: In Formula I, R 1 and R 2 are the same or different, each independently selected from hydrogen, halogen, C1-C 20 Preferably, R 1 and R 2 Each of the heteroatoms comprises one or a combination of two or more selected from halogen, N, O, S, P and Si; preferably, R 1 and R 2 Bonded to each other to form a ring.

2. The catalyst component according to claim 1, wherein In Formula I, R 1 and R 2 the same or different, each independently selected from H, halogen, the following substituents with less than 20 carbon atoms: straight-chain or branched alkyl, cycloalkyl, alkenyl, ester, phenyl, alkylphenyl, phenylalkyl, indenyl, benzyl, halogenated alkyl, alkyl containing heteroatoms, halogenated cycloalkyl, cycloalkyl containing heteroatoms, halogenated phenyl, phenyl containing heteroatoms, halogenated alkylphenyl, alkylphenyl containing heteroatoms, halogenated phenylalkyl, phenylalkyl containing heteroatoms, halogenated indenyl, indenyl containing heteroatoms, halogenated benzyl, benzyl containing heteroatoms, heterocyclic aromatic substituents; the heteroatoms include one or a combination of two or more of N, O, S, P, and Si.

3. The catalyst component according to claim 2, wherein In Formula I, R 1 and R 2 are each independently selected from H, halogen, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, cyclopentyl, n-hexyl, cyclohexyl, heptyl, octyl, nonyl, decyl, C 11 -C 20 The straight-chain or branched alkyl group of 20 carbon atoms or the following substituents within 20 carbon atoms: alkenyl, phenyl, m-chlorophenyl, p-chlorophenyl, o-chlorophenyl, m-methoxyphenyl, p-methoxyphenyl, o-methoxyphenyl, p-methylphenyl, p-nitrophenyl, m-nitrophenyl, benzyl and its derivatives, phenethyl and its derivatives, furyl, pyrrolyl, thienyl and indenyl.

4. The catalyst component according to claim 1, wherein The chlorendic acid ester internal electron donor includes dimethyl chlorendic acid, diethyl chlorendic acid, di-n-propyl chlorendic acid, diisopropyl chlorendic acid, di-n-butyl chlorendic acid, diisobutyl chlorendic acid, di-tert-butyl chlorendic acid, di-n-pentyl chlorendic acid, diisopentyl chlorendic acid, dicyclopentyl chlorendic acid, di-n-hexyl chlorendic acid, dicyclohexyl chlorendic acid, diheptyl chlorendic acid, dioctyl chlorendic acid, dinonyl chlorendic acid, didecyl chlorendic acid, diundecyl chlorendic acid, didodecyl chlorendic acid, ditridecyl chlorendic acid, ditetradecyl chlorendic acid, dipentadecyl chlorendic acid, dihexadecyl chlorendic acid, diheptadecyl chlorendic acid, dioctadecyl chlorendic acid, The invention can be selected from the group consisting of di(nonadecyl)chlorendic acid ester, di(eicosyl)chlorendic acid ester, diphenyl chlorendic acid ester, di-m-chlorophenyl chlorendic acid ester, di-p-chlorophenyl chlorendic acid ester, di-o-chlorophenyl chlorendic acid ester, di-p-tolyl chlorendic acid ester, di-m-tolyl chlorendic acid ester, di-o-tolyl chlorendic acid ester, di-(mesitylene) chlorendic acid ester, di-p-methoxyphenyl chlorendic acid ester, di-m-methoxyphenyl chlorendic acid ester, di-o-methoxyphenyl chlorendic acid ester, di-p-nitrophenyl chlorendic acid ester, di(α-furan)methyl chlorendic acid ester, di(5-pentene) chlorendic acid ester, di(α-thiophene) chlorendic acid ester, dibenzyl chlorendic acid ester, diphenylethyl chlorendic acid ester, dicinnamyl chlorendic acid ester, ditetrahydrofurfuryl chlorendic acid ester, and di(1-indenyl) chlorendic acid ester.

5. The catalyst component according to any one of claims 1 to 4, wherein The catalyst component comprises a titanium compound, a magnesium compound, and an internal electron donor as shown in formula I; The precursor of the magnesium compound is selected from X n Mg(OR a ) 2-n 、MgCl2·mR a OH, R a 2-n MgX n , MgCl2 / SiO2, MgCl2 / Al2O3, a mixture of magnesium halide and titanium alkoxide, or a combination of two or more thereof, wherein m is 0.1-6, 0≤n≤2, X is a halogen, R a C1-C 20 The hydrocarbon group; The general formula of the titanium compound is TiX N (OR b ) 4-N , where R b C1-C 20 The hydrocarbon group is: X is halogen, and N is 1-4.

6. The catalyst component according to claim 5, wherein The magnesium compound is an alcoholate of magnesium dihalide; Alternatively, the magnesium compound is a liquid magnesium compound; Alternatively, the magnesium compound is a derivative of a magnesium dihalide molecule in which at least one halogen atom is replaced by a hydrocarbonoxy group or a halogenated hydrocarbonoxy group; preferably, it is a hydrocarbonoxy magnesium compound; more preferably, it is an alkoxy magnesium and / or an aryloxy magnesium.

7. The catalyst component according to claim 5, wherein The titanium compound includes one or a combination of two or more of titanium tetrachloride, titanium tetrabromide, titanium tetraiodide, and alkoxy titanium halide; Preferably, the alkyl titanium halide includes one or a combination of two or more of methoxytitanium trichloride, ethoxytitanium trichloride, propoxytitanium trichloride, n-butoxytitanium trichloride, dimethoxytitanium dichloride, diethoxytitanium dichloride, dipropoxytitanium dichloride, di-n-butoxytitanium dichloride, trimethoxytitanium chloride, triethoxytitanium chloride, tripropoxytitanium chloride, and tri-n-butoxytitanium chloride; Preferably, the titanium compound is titanium tetrachloride.

8. The catalyst component according to claim 5, wherein The molar ratio of the internal electron donor represented by formula I to the magnesium compound is 0.01-5.0:1, preferably 0.05-3.0:1, and the magnesium compound is calculated as magnesium element.

9. A catalyst for olefin polymerization, comprising the catalyst component according to any one of claims 1 to 8 and an organic aluminum compound.

10. The catalyst according to claim 9, wherein The general formula of the organoaluminum compound is AlR c p X (3-p) , where R c is hydrogen or C1-C 20 A hydrocarbon group, X is a halogen, and p is an integer of 0≤p≤3; Preferably, the organoaluminum compound comprises one or a combination of two or more of trialkylaluminum compounds, alkylaluminum halides, alkylaluminum hydrides, alkylaluminum sesquichlorides, and alkylaluminoxanes; Preferably, the trialkylaluminum compound includes one or a combination of two or more of trimethylaluminum, triethylaluminum, triisobutylaluminum, tri-n-butylaluminum, tri-n-hexylaluminum, and trioctylaluminum; the alkylaluminum halide includes AlEt2Cl; the alkylaluminum sesquichloride includes Al2Et3Cl3; Preferably, the organoaluminum compound is a mixture of AlEt2Cl and Al2Et3Cl3.

11. The catalyst according to claim 9, wherein The molar ratio of the organic aluminum compound to the titanium atom in the catalyst component is 1-1000:1:1, preferably 50-800:

1.

12. The catalyst according to claim 9, wherein The raw material composition of the catalyst also includes an external electron donor.

13. The catalyst according to claim 12, wherein The external electron donor is a siloxane compound.

14. The catalyst according to claim 13, wherein The general formula of the siloxane compound is R' t Si(OR”) 4-t , wherein R' and R" are each independently selected from C1-C 18 A hydrocarbon group, t is an integer of 0≤t≤3; Preferably, R' and R" each contain a heteroatom; Preferably, the heteroatom includes one or a combination of two or more of N, O, S, P and Si.

15. The catalyst according to claim 12, wherein The molar ratio of silicon in the external electron donor to titanium in the catalyst component is 0.002-100:1, preferably 0.01-20:1, and more preferably 0.01-5:

1.

16. Use of the catalyst according to any one of claims 9 to 15 in olefin polymerization; Preferably, the olefin includes one or a combination of two or more of ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 3-methyl-1-butene, 4-methyl-1-pentene, butadiene, vinylcyclopentene, and vinylcyclohexene; Preferably, the polymerization comprises ethylene and / or propylene polymerization; Preferably, the polymerization comprises homopolymerization or copolymerization.

17. The use according to claim 16, wherein: The polymerization temperature is ≤200°C, preferably 20-100°C, more preferably 40-80°C; The polymerization pressure is ≤10 MPa, preferably 0.3-5 MPa.

Citation Information

Patent Citations

  • Diethers usable in the preparation of Ziegler-Natta catalysts and their preparation

    EP0361493A1

  • Diethers suitable for use in the preparation of Ziegler-Natta catalysts

    EP0728724A1

  • Carbene donor-modified Ziegler-Natta catalysts

    US20060128558A1

  • Catalyst components and catalysts for the polymerization of alpha-olefins

    US4399054A

  • Process for preparing spheroidally shaped products, solid at room temperature

    US4469648A